Поняття як важливий елемент формально-логічної структури думки - Шавлак, А. (ХНУРЕ, 2021)
This thesis examines the Variation of the Concept in logic. All mistakes that can be made have been analyzed. The types of the Concept are considered in more detail and the meaning of the definition itself is revealed. Particular attention is drawn to the definition of the Concept Variation, its types and examples, given for a more precisely formed understanding of the Concept Variation.
Keywords: філософія; структура думки